2019
DOI: 10.2139/ssrn.3383408
|View full text |Cite
|
Sign up to set email alerts
|

Working from Home: Heterogeneous Effects on Hours Worked and Wages

Abstract: Working from home (WfH) has become much more common since the early 2000s.We exploit the German Socio-Economic Panel between 1997 and 2014 to investigate how such a work arrangement affects labour market outcomes and life satisfaction.We find that childless employees work an extra hour per week of unpaid overtime and report higher satisfaction after taking up WfH. Among parents, WfH reduces the gender gap in working hours and monthly earnings, as contractual hours increase more among mothers. Hourly wages, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 47 publications
0
26
0
2
Order By: Relevance
“…In addition, staying connected outside of core work hours has been shown to produce social exclusion and create persistent problems at home so much as to necessitate coping strategies to create boundaries between work and family activities (Tietze 2002;Myrie and Daly 2009). Yet, Arntz, Yahmed, and Berlingieri (2019) found no significant effects of WFH on job or life satisfaction for working parents living in Germany.…”
Section: Wage Effects Of Teleworkmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, staying connected outside of core work hours has been shown to produce social exclusion and create persistent problems at home so much as to necessitate coping strategies to create boundaries between work and family activities (Tietze 2002;Myrie and Daly 2009). Yet, Arntz, Yahmed, and Berlingieri (2019) found no significant effects of WFH on job or life satisfaction for working parents living in Germany.…”
Section: Wage Effects Of Teleworkmentioning
confidence: 73%
“…Using an instrumental variables technique and U.S. data, Heywood, Seibert, and Wei (2007) found a positive wage differential for WFH but not for other workplace practices. Using the German Socio-Economic Panel and a fixed-effects model, Arntz, Yahmed, and Berlingieri (2019) show that women earned higher wages only if they switched into jobs that allowed WFH while men earned higher wages when they worked from home even if they remained with the same employer. They also found that the share of women in jobs permitting WFH expanded more rapidly between 1997 and 2014 than the share of men in jobs permitting work from home, and that mothers' labor force attachment increased with WFH.…”
Section: Wage Effects Of Teleworkmentioning
confidence: 99%
“…Bloom et al (2015) found job satisfaction to increase by working from home. WFH is also positively associated with family-life satisfaction (Arntz, Sarra, and Berlingieri 2019;Virick, DaSilva, and Arrington 2010). Kazekami (2020) studied the productivity of workers in Japan and discovered that telework increases life satisfaction.…”
Section: /11/2020mentioning
confidence: 99%
“…Even for the gender pay gap, although widely studied, there is not a clear evidence of the effect of WFH. Gariety and Shaer (2007), Bloom et al (2015), Arntz et al (2019), and Angelici and Profeta (2020) point out that WFH may reduce (or at least not increase) wage differences between male and female workers. On the other hand, Weeden (2005), Goldin (2014), and Bertrand (2018) display results in the opposite direction.…”
Section: Introductionmentioning
confidence: 99%